PERAN MEDIA LOKAL “INFO PURWOKERTO” DALAM PENYEBARAN INFORMASI PUBLIK DI PURWOKERTO - Sabila Dini (CALACCITRA: JURNAL FILM DAN TELEVISI, 2026)
This research aims to find out how the role of local media "Info Purwokerto" in the dissemination of public information in Purwokerto. This study investigates the role of local media "Info Purwokerto" in contributing to the dissemination of public information in Purwokerto. Data was collected through in-depth interviews with "Info Purwokerto" managers, local government representatives and local community members. This data collection method uses a descriptive qualitative approach. According to the research results, "Info Purwokerto" plays an important role as a reliable source of information for the people of Purwokerto. This media can disseminate various types of public information, including government policies, local events, and emergency situations. In addition, "Info Purwokerto" is an interactive platform that enables two-way communication between the government and the community, aiming to increase public participation and information transparency. However, issues such as ensuring the truth of information and preventing the spread of hoaxes are still a major concern. This study recommends increasing cooperation between "Info Purwokerto" and government institutions and media literacy training for the community to maximize the role of the media.